Pengaruh Kualitas Pelayanan, Produk dan Harga Terhadap Keputusan Penggunaan Jasa Asuransi AJB Bumiputera 1912 Kantor Cabang Eksekutif Semarang - Tri Maduma Siburian; Nawazirul Lubis; Hari Susanta Nugraha (Universitas Diponegoro, 2013)
Development needs of an increasingly complex underwriting risk and market competition sharpened cause must be competitive Bumiputera 1912 to show its superiority and grab the attention of the policyholder. People who will make a decision in choosing Bumiputera insurance will consider various things before buying. Consideration, among others, influenced by the quality of service, products, and prices are set by the company. This study to determine the problems that arises is whether there is influence between quality of service, products and prices on the decision to use insurance services. This type of research is explanatory research with a sample of 100 respondents taken by systematic sampling technique. The data were analyzed qualitatively and quantitatively using validity, reliability, cross tables, simple linear regression, multiple linear regression, t test and F test and the coefficient of determination with SPSS ver 17.0. Given the simple linear regression equation between quality of service and service usage decision is Y = 4.404 + 0.169 X1. Linear regression equation between products with the decision to use services is Y = 8.009 + 0.465 X2. Linear regression equations between price and service usage decisions is Y = 11.709 + 0.339 X3. Based on these equations can be seen that there is a partial positive influence between each variable X to variable Y. Multiple regression analysis is Y = 1.124 + 0.117 X1 + 0.255 X2 + 0.213 X3 so it can be seen that the variable X simultaneously positive effect on the variable Y, and which have the greatest effect is the variable quality of service. Hypothesis testing shows that the variable quality of service, products and prices, affect the decision to use services. This is demonstrated by obtaining t count variable service has 4.473 t count, product 4.590, 3.289 price variable. As for the F test obtained F count of 12.262. And all of these variables were tested at a significance level of 5%. The hypothesis is accepted. Conclusions and suggestions are obtained respondents felt that the quality of care in good categories, products in good categories, and prices in the category of less affordable for a minority of respondents. Companies should consider the price (insurance premiums) to become more affordable again by prospective policyholders in general, the economically capable alsomiddle and lower economic classes to enjoy the protection of an insurance.